The Perception of Idyllic Rural Areas in Slovenia - Virant, Zala; Konečnik Kotnik, Eva (Journal for Geography, 2022)
The Perception of Idyllic Rural Areas in Slovenia The transition of society from a traditional to a modern form brought changes in the structure of society and caused phenomena such as urbanization, fast pace of life and alienation, which affect changes in our value system. One of the areas that we consequently as a society are beginning to value differently is the concept of the countryside. Today's society relies heavily on industry and technology as a driver of development, which has caused the countryside to change its purpose, functions, symbolism, characteristics and identity. Modern society quite often associates the concept of the countryside with a beautiful, peaceful, clean and happy living environment that can be characterized as idyllic. The emergence of an idyllic idea of the countryside can further influence changes in the concrete rural area. The purpose of the paper is to show that the countryside can be studied as a social construct, which is influenced by the interpretation of the surroundings or wider society. We want to show the characteristics of the perception of the countryside in Slovenia, or to present the evaluation of Slovenian rural regions based on the opinion of the inhabitants of Slovenia, and to show how the social perception of space can affect the changing of various characteristics of the region and the changing pattern of behaviour of residents and visitors.
Keywords: perceptions; idyllic countryside; rural geography; Slovenija